". . . If You're Not Part of the Institution You Fall by the Wayside": Service Providers' Perspectives on Moving Young Men From Disconnection and Isolation to Connection and Belonging. Issue 2 (March 2018) - Grace, Billy; Richardson, Noel; Carroll, Paula
There have been increasing calls for more gender-specific service provision to support young men's (20-29 years) mental health and well-being. In Ireland, young men are the demographic group that are most likely to die by suicide but among the least likely to seek help. This study sought to investigate service providers' perspectives on the factors that support or inhibit young men from engaging in services targeted at supporting their mental/emotional well-being. Qualitative methodologies (focus groups, n = 9; interviews, n = 7) were used for this study. Disconnection from family and community was identified as a key indicator of "at-risk" groups of young men who, more typically, had experienced significant disruption in their lives. The discord between demands and expectations facing young men on one hand, and insufficient life-management and coping skills on the other, left many young men vulnerable and bereft. The desire to save face and preserve one's masculine identity was linked to young men's reluctance to seek help when feeling down. There was a strong consensus that there could be no shortcuts to [re]connecting with young men. While sport, technology, and social media were cited as appropriate media in which to engage young men, the essence of sustained connection revolved around creating safety, trust, rapport, and meaningful relationships. The findings from this study have informed the development of a Train the Trainer program ("Connecting with Young Men"), which is currently being delivered to service providers in Ireland and which may have implications for service provision elsewhere.